Gastric-type mucinous endocervical adenocarcinomas: A case report and literature review - Lu, Junling; Na, Jing; Li, Ya; Wang, Xinyou; Wang, Jun; Han, Shichao (Frontiers in Cellular and Infection Microbiology, 2022)
Gastric-type mucinous endocervical adenocarcinomas (GAS) are new variant types of cervical adenocarcinomas according to the 2014 World Health Organization (WHO) classification. GAS is a unique disease that can be differentiated from typical adenocarcinomas—it is less common and more aggressive and likely to have deep invasion and horizontal diffusion, invasion of the uterus and vagina, early distant metastases, and a lower 5-year survival rate compared to the usual-type cervical cancer. At present, initial treatment and postoperative adjuvant therapy are not conclusive, but early detection and early treatment are a consensus that can improve prognosis. Most of its occurrence has nothing to do with human papillomavirus (HPV) infection. Whether it is only negative for the subtypes that can be detected at present and whether it may be an unknown subtype of infection need to be further explored in the future. The clinical symptoms commonly include aqueous secretion, lower abdominal pain, and elevated serum carbohydrate antigen-19-9 (CA19-9) levels, which may be helpful for diagnosis. MRI and PET-CT can help to describe the characteristics of lesions and judge the state of the systemic metastasis. We believe that early detection and surgical treatment will give patients more benefits. Looking for potential gene and molecular changes and establishing biomarkers to identify molecular targets will be the key to early identification and target therapy.